Pagan Studies: In Defense of Pluralism - Ezzy, Douglas (Pomegranate, 2015)
Pagan studies should allow the inclusion of religionist ideas and concepts within its academic oeuvre. Such concepts and ideas have been, and will probably continue to be, productive empirically and theoretically. Religious language and concepts can provide new and interesting ways of seeing and understanding the world that are empirically insightful. Further, the academic study of religion should practice a “deep pluralism” in which religionist ideas sit beside critical-naturalist atheism. This arises out of a presumptive humility, recognising that one’s own perspective may not be the final and complete way of understanding all things.